Cost‐effectiveness of patient navigation to increase adherence with screening colonoscopy among minority individuals. Issue 7 (9th December 2014) - Ladabaum, Uri; Mannalithara, Ajitha; Jandorf, Lina; Itzkowitz, Steven H.
<x xml:space="preserve">Abstract</x> BACKGROUND Colorectal cancer (CRC) screening is underused by minority populations, and patient navigation increases adherence with screening colonoscopy. In this study, the authors estimated the cost‐effectiveness of navigation for screening colonoscopy from the perspective of a payer seeking to improve population health. METHODS A validated model of CRC screening was informed with inputs from navigation studies in New York City (population: 43% African American, 49% Hispanic, 4% white, 4% other; base‐case screening: 40% without navigation, 65% with navigation; navigation costs: 29 per colonoscopy completer, 21 per noncompleter, 3 per non‐navigated individual). Two analyses compared: 1) navigation versus no navigation for 1‐time screening colonoscopy in unscreened individuals aged ≥50 years; and 2) programs of colonoscopy with versus without navigation versus fecal occult blood testing (FOBT) or fecal immunochemical testing (FIT) for individuals ages 50 to 80 years. RESULTS In the base case: 1) 1‐time navigation gained quality‐adjusted life‐years (QALYs) and decreased costs; 2) longitudinal navigation cost 9800 per QALY gained versus no navigation, and, assuming comparable uptake rates, it cost 118, 700 per QALY gained versus FOBT but was less effective and more costly than FIT. The results were most dependent on screening participation rates and navigation costs: 1) assuming a 5% increase in screening uptake with navigation, and a navigation cost of 150 per completer, 1‐time navigation cost 26, 400 per QALY gained; and 2) longitudinal navigation with 75% colonoscopy uptake cost <25, 000 per QALY gained versus FIT when FIT uptake was <50%. Probabilistic sensitivity analyses did not alter the conclusions. CONCLUSIONS Navigation for screening colonoscopy appears to be cost‐effective, and 1‐time navigation may be cost‐saving. In emerging health care models that reward outcomes, payers should consider covering the costs of navigation for screening colonoscopy. Cancer 2015;121:1088–1097. © 2014 American Cancer Society.